Systematic review of Promitobates Roewer, 1913 and cladistic analysis of Mitobatinae Simon, 1879 (Arachnida: Opiliones: Gonyleptidae) - Bragagnolo, Cibele; Pinto-Da-Rocha, Ricardo (Zootaxa, 2012)
A cladistic analysis of the genera of Mitobatinae and species of Promitobates Roewer, is presented. Only one equally mostparsimonious tree was obtained (L=273, CI=0.36; RI=0.73) from a data matrix of 77 equally weighted characters.Mitobatinae is recovered as a monophyletic group, with low Bremer support, sister to (“Pachylinae” + Bourguyiinae).Despirus parvulus, Roewer is sister to the remaining mitobatines, which are divided into two major clades: [1] one thatpossesses a roughly rectangular body, and males and females with coxa and trochanter IV without large apophyses,including the genera Ischnotherus Kury, Encheiridium Kury, Metamitobates Roewer, Ruschia Mello-Leitão, MitobatulaRoewer, and Mitobates Sundevall; and [2] one that possesses the body roughly pyriform, with evident sexual dimorphismof coxa and trochanter IV, in which males have a large apophysis on coxa IV and tubercles on trochanter IV, including thegenera Discocyrtoides Mello-Leitão, Longiperna Roewer, Neoancistrotus Mello-Leitão, and Promitobates. A taxonomicreview of Promitobates and a new classification of its species, supported by results of the cladistic analysis, are presented. Based on these results P. intermedius (Mello-Leitão) comb. n., and P. nigripes (Mello-Leitão) comb. n., are revalidatedand removed from the synonymy of P. ornatus (Mello-Leitão). The following synonymies are proposed: Leonardosianitida Mello-Leitão = P. nigripes (Mello-Leitão), Ancistrotellus hauseri Šilhavý = P. viridigranulatus (Soares & Soares),P. margaritatus Roewer, 1931 = P. ornatus (Mello-Leitão, 1922) and P. mendax H. Soares, 1945 = P. hatschbachi H.Soares. Promitobates granulosissimus Mello-Leitão and P. hexacanthus Koch are considered species inquirendae. Fournew species from Brazil are described: P. ale sp. n. (type locality: Ano Bom, Santa Catarina); P. trapista sp. n. (typelocality: Reserva Morro Grande, São Paulo); P. weissbier sp. n. (type locality: Ribeirão Pires, São Paulo), and P. lager sp. n. (type locality: Jacarepaguá, Rio de Janeiro).